Optimizing the Blue Ocean Strategy to Enhance Innovation, Customer Satisfaction, and Business Performance at Cafe Camellia - Purnamayanti, Ida Ayu Gede Wiwik; Diwya, Ketut Gede Sri; Arnawa, Ida Bagus Ketut Surya; Dewi, Made Vera Kristanti (Universitas Pendidikan Nasional, 2025)
This research was conducted to address the decline in revenue and profit experienced by Cafe Camellia due to decreased consumer purchasing power and increasing market competition. The study focuses on strategies to enhance business performance through product innovation, interior design improvement, and human resource management development. The research problems include identifying effective strategies to boost revenue and profit, as well as examining how the implementation of product innovation, attractive interior design, and sound HR management can improve customer satisfaction while reducing employee turnover. A mixed-methods approach was employed, combining qualitative and quantitative methods through SWOT analysis, the application of Blue Ocean Strategy, and the Design Thinking process to generate innovative and market-relevant solutions. The findings indicate that a strategic combination of customer-oriented product innovation, improvements in café layout and atmosphere, and more professional, development-focused human resource management significantly enhances customer loyalty and workforce stability, thereby contributing to increased revenue and profitability for Cafe Camellia. In conclusion, the synergy between product innovation, interior design, and human resource management serves as a key factor in addressing current business challenges and forms a strategic foundation for the future management of Cafe Camellia.